2015
DOI: 10.1371/journal.pone.0125997
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Predicts 30 Day Mortality in Hospitalised Cats

Abstract: Vitamin D insufficiency, defined as low serum concentrations of the major circulating form of vitamin D, 25 hydroxyvitamin D (25(OH)D), has been associated with the development of numerous infectious, inflammatory, and neoplastic disorders in humans. In addition, vitamin D insufficiency has been found to be predictive of mortality for many disorders. However, interpretation of human studies is difficult since vitamin D status is influenced by many factors, including diet, season, latitude, and exposure to UV r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…It has been demonstrated that low serum concentrations 25(OH)D are associated with an increased risk of 30 day mortality in sick cats (Titmarsh et al . ). In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been demonstrated that low serum concentrations 25(OH)D are associated with an increased risk of 30 day mortality in sick cats (Titmarsh et al . ). In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al .…”
Section: Discussionmentioning
confidence: 97%
“…Less is known about the relationship between vitamin D status and disease outcomes in cats although studies have documented low serum 25 (OH)D levels in diseases including inflammatory bowel disease, gastrointestinal lymphoma and mycobacterial infection (Lalor et al 2012(Lalor et al , 2014. It has been demonstrated that low serum concentrations 25(OH)D are associated with an increased risk of 30 day mortality in sick cats (Titmarsh et al 2015). In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on all‐cause mortality in cats found that cats with low serum 25(OH)D concentrations had a significant higher risk of mortality (Titmarsh et al . ). The study evaluated the ability of a range of clinical and biochemical data including sex, age, breed, appetite, total white blood cells, packed cell volume and serum concentrations of albumin, total calcium, creatinine, sodium, potassium and 25(OH)D concentration to predict mortality by 30 days.…”
Section: Vitamin D – An Overviewmentioning
confidence: 97%
“…A recent study on all-cause mortality in cats found that cats with low serum 25(OH)D concentrations had a significant higher risk of mortality (Titmarsh et al . 2015b ).…”
Section: Vitamin D and Mortalitymentioning
confidence: 99%
“…Vitamin D is a critical component in the development and maintenance of skeletal health 1 . However, current research suggests that vitamin D may also have wider biomedical effects, with studies linking vitamin D insufficiency to increased risk of mortality in humans and companion animals [2][3][4] , as well as reproductive failure, low birth weight, infertility and reduced litter sizes in humans, rats and mice [5][6][7][8] . This link suggests that vitamin D status may be associated with fitness in natural populations, yet there have been no investigations into the causes and consequences of its variation in wild populations.…”
Section: Introductionmentioning
confidence: 99%